Formulation and Characterization of Analog Rice Using Arrowroot (Maranta arundinacea L.) and Hibiscus Flower (Hibiscus rosa sinensis L.) - Arlita Leniseptaria Antari; Indah Saraswati; Eva Annisa; Anfa Adnia Fatma (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Efforts to reduce high-carbohydrate consumption from rice include the development of analog rice from alternative sources such as arrowroot tubers (Maranta arundinacea L.). Proper formulation is crucial for producing analog rice with optimal quality, taste, and characteristics resembling conventional rice, while maintaining functional properties to meet carbohydrate and nutritional needs. Hibiscus (Hibiscus rosa-sinensis L.), which is rich in flavonoids, saponins, and anthocyanins, can enhance these formulations. Objective: The objective of this study was to evaluate the composition of a blend of arrowroot tubers (M. arundinacea L.) and hibiscus (H. rosa-sinensis L.) as a rice substitute. Methods: This study used 50 untrained panelists to conduct organoleptic tests on the shape, color, aroma, taste, and texture of rice and analog rice using five formulas (F1, F2, F3, F4, and F5). Furthermore, physical characteristics were tested, including the color index, 1000-grain weight, bulk density, and starch digestibility. Results: The characteristics test proved that all analog rice formulas had an average hedonic score in the range of 3.73-3.90; lower bulk Density than rice with a bulk density of 0.83 ± 0.02 g/mL; starch digestibility in the range of 0.62-0.67 g/mL; and has a yellow-red color range. Conclusion: The best and most preferred rice analog is Formula 5 (F5), with a composition of arrowroot tubers 57.8%, hibiscus 5.1%, mocaf 12.6%, GMS 0.6%, and water 23.9%.